2018
DOI: 10.3390/en11092348
|View full text |Cite
|
Sign up to set email alerts
|

RANS and Hybrid RANS-LES Simulations of an H-Type Darrieus Vertical Axis Water Turbine

Abstract: Nowadays, the global energy crisis has encouraged the use of alternative sources like the energy available in the water currents of seas and rivers. The vertical axis water turbine (VAWT) is an interesting option to harness this energy due to its advantages of facile installation, maintenance and operation. However, it is known that its efficiency is lower than that of other types of turbines due to the unsteady effects present in its flow physics. This work aims to analyse through Computational Fluid Dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Good results can be obtained with LES and DES methods, but they require much more calculation than RANS does. RANS and hybrid RANS-LES were suitable for the turbulent flow dynamics on a small scale [57]. LES was used to solve the turbulence itself in large and complex flows, and the vortex could be used to illustrate interactions between fluid and blades [58].…”
Section: Methodsmentioning
confidence: 99%
“…Good results can be obtained with LES and DES methods, but they require much more calculation than RANS does. RANS and hybrid RANS-LES were suitable for the turbulent flow dynamics on a small scale [57]. LES was used to solve the turbulence itself in large and complex flows, and the vortex could be used to illustrate interactions between fluid and blades [58].…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the best turbine type under the same configurations, considering that the Darrieus and Gorlov rely on the lift force principle and the Savonius relies on the drag force principle. While making the analyses, the turbine rotation area was modeled with a dynamic mesh, rather than the sliding mesh technique used in many previous studies [38,[46][47][48]. In this method, rather than assigning a specific rotation angle to the turbine, the model is run according to the angular velocity of the turbine, which changes depending on the water flow velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations have thus continued to improve in their capacity to resolve the salient dynamics in the wakes of VAWTs. Mejia et al [6] used URANS (K − w SST), DES (detached eddy simulation) and DDES (delayed detached eddy simulation) methods to calculate the aerodynamic performances of an H-type Darrieus VAWT. By plotting Q isosurfaces, they demonstrated that DES and DDES are both effective in identifying vortices.…”
Section: Introductionmentioning
confidence: 99%